Evaluation of the Antifungal and Antiproliferative Properties of the Lichen Roccella tinctoria DC. Extracts and Main Components - Claudio Frezza; Dalia Rosa Fraioli; Francesca Conti; Roberta Maria Nicolosi; Luigi Scipione; Ilaria Serafini; Rita Petrucci; Paola Di Matteo; Daniele Rocco; Silvia Di Giacomo; Antonella Di Sotto; Graziana Bonincontro; et al. (MDPI AG, 2024)
In this work, phytochemical analysis on different extracts of Roccella tinctoria DC. was reported using different techniques with respect to the past. Twenty volatile and three non-volatile compounds were identified, some of which were found in this species for the first time. The methanolic extracts and their non-volatile components were then evaluated for their antitumor effects in cancerous A549 and Mz-ChA-1 cells and for their tolerability in non-cancerous BEAS-2B and H69 cells, showing IC50 values from 94.6 µg/mL to 416.4 µg/mL, in general. The same extracts and compounds were also tested for their antifungal effects in Candida albicans, with only compound 2 being active, with an MIC50 value of 87 µg/mL. In addition, they were tested for their anti-Candida adhesion activity, anti-Candida biofilm formation, and anti-Candida mature biofilm inhibition, with efficacy percentages generally above 50% but not for all of them. Lastly, the DF3 extract and compounds 1-2 were tested in vivo according to the Galleria mellonella survival assay, showing positive mortality rates above 50% at different concentrations. All these biological assays were conducted on this species for the first time. Comparisons with other lichens and compounds were also presented and discussed.